(untitled) (Research, Society and Development, 2022)
This essay aims to assess the perception of professors about remote teaching in the medical course during SARS-CoV-2 pandemic. This is a quantitative research approach where a convenience sampling was chosen taken from lectures of a private medical school. The population consisted of 90 professors who answered a structured questionnaire with Likert scale. Among the sample, 47.8% of professors stated difficulties in adapting to emergency remote teaching, however, 92.2% gave importance to institutional training for adaptations to active methodologies. Most of them considered synchronous activities important, although agreed that remote learning generates discouragement in students, but can contribute to learning, without substituting face-to-face tuition. Remote learning is possible and was important in the pandemic however, the return to face-to-face activities is a fundamental requirement for medical formation.